Preachin' the blues the life and times of Son House - Beaumont, Daniel E. (Oxford University Press, 2011)
In June of 1964, three young, white blues fans set out from New York City in a Volkswagen, heading for the Mississippi Delta in search of a musical legend. So begins Preachin' the Blues, the biography of American blues signer and guitarist Eddie James ""Son"" House, Jr. (1902 - 1988). House pioneered an innovative style, incorporating strong repetitive rhythms with elements of southern gospel and spiritual vocals. A seminal figure in the history of the Delta blues, he was an important, direct influence on such figures as Muddy Waters and Robert Johnson. The landscape of Son House's life and th
Keywords: House, Son; Blues musicians : United States : Biography